Radioprotective role of 50 % watermelon juice against low dose radiation-induced oxidative DNA damage and apoptosis in ICR mice / Mohd Khairul Amran Mohammad - Mohammad, Mohd Khairul Amran (2015)
Watermelon is a natural product that contains high level of antioxidants and may prevent oxidative damage and apoptosis following an exposure to ionising radiation. The present study aimed to investigate the radioprotective role of 50 % watermelon juice against low dose radiation (LDR)-induced oxidative DNA damage and apoptosis in ICR mice. Eighteen male ICR mice were equally divided into three groups: control (Cx), radiation (Rx) and supplementation (Tx) groups (n=6). Cx and Rx received filtered tap water while Tx was supplemented with 50 % watermelon juice ad libitum for 28 consecutive days. A total body irradiation of 100 |iGy X-ray was given to Rx and Tx on day 29. Liver and lung tissues were assessed for the levels of reactive oxygen species (ROS) and DNA damage. The alteration of p53, Bax, and Bcl-2 protein expressions were determined followed by ultrastructural changes confirmation. Present study showed exposure to LDR was able to enhance oxidative DNA damage and alter the expression of p53, Bax and Bcl-2. The onset of apoptosis following LDR exposure was confirmed by ultrastructure evaluation of nucleus via transmission electron microscope (TEM). Interestingly, supplementation with 50 % watermelon juice prior to LDR exposure was able to diminish the levels of oxidative DNA damage compared to Cx. Additionally, mice in Tx showed significant restoration of altered apoptotic related protein expressions and reverted the abnormal structural changes to near normal morphology (Cx). These findings propose that 50 % watermelon juice may serve as an effective natural radioprotective agent against LDR-induced oxidative DNA damage and alteration of apoptotic-related protein expressions in ICR mice.